Complex Neutrosophic Approach for Uncertainty Management in Employment Competence for Higher Vocational College Students - Shuo Du; Lijuan Zhao (Neutrosophic Sets and Systems)
In an era of rapid technological revolutions as well as ever-changing job market dynamics, the analysis of employment competence for higher vocational college students becomes a complicated challenge. Legacy methods become unable to manage the intrinsic uncertainty related to workforce readiness, skill relevancies, and career decision-making. In this work, we propose a multi-criteria complex neutrosophic approach integrating for optimization and uncertainty management of vocational student employment. Our approach provides a novel application of the Interval Complex Neutrosophic Set (ICNS) to handle indefinite, hesitant, and inconsistent information in vocational student employment. It also presents a novel ICNS de-neutrosophication method to provide representative and expressive scoring of ICNS decisions. Then, algorithmic analytical weighting is applied to infer the significance of ICNS-valued criteria. Following, the ICNS-VIKOR method is integrated to compute evaluation results and rank vocational employment strategies according to either compromise Measure, Regret Measure, or Q-VIKOR Index scores for each alternative. We introduce a real-world case study to optimize the evaluation of different vocational employment configurations based on ten competing criteria. The quantitative and qualitative results indicate that our methodology offers a systematic and reliable decision-support tool, that effectively optimizes trade-offs as well as uncertain judgments from policymakers, career advisors, and industry recruiters. The proof-of-concept analysis highlighted the best-ranked alternative while offering intuitions about the sensitivity of the decision process.